MANAGEMENT TREATMENT OF PROLIFERATIVE LUPUS NEPHRITIS: A SYSTEMATIC REVIEW - Frida Setiawan, Yenny (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
One common and dire manifestation that should be looked for in SLE is the involvement of the kidneys, known as lupus nephritis (LN). Proliferative lupus nephritis is the one of types lupus nephritis which is currently still a challenge in its management. prevent nephron damage, and CKD especially end-stage kidney disease (ESKD) by administering immunosuppressive agents to improve outcomes and prognosis. This qualitative study with a systematic review approach carried out an electronic search in Medline (PubMed interface), Google Scholar, Scopus, Elsevier and Web of Science, using the keyword. Literatures were extracted, duplicate screening, and pooled analysis finally included 10 studies in the qualitative study. The clinical trial literature in the last five years includes tacrolimus, azathioprine, rituximab, cyclosporine, belimumab, leflunomide, fish oil, obinutuzumab, and voclosporin which can be combined with standard therapy. Other literature also recommends abatacept, laquinimod, ocrelizumab, sirukumab, misoprostol, plasma exchange, IV immunoglobulin, and stem cell therapy which can be used for the proliferative therapy of lupus nephritis.